Agricultural greenhouse gas emission factors [SAMPLES Database] - Richards, Meryl; Costa Junior, Ciniro (2024)
This document contains agriculture emission factors collected between 2000 and 2020 from published datasets that was housed on the Standard Assessment of Agricultural Mitigation Potential and Livelihoods (SAMPLES) website managed by the former CGIAR Research Program Climate Change, Agriculture and Food Security (CCAFS). Users were able to download site-specific emission factors and associated agroecological data for use in greenhouse gas accounting or inventories and find links and contact information to access full datasets for use in biogeochemical modeling. It was also encouraged that anyone conducting greenhouse gas (GHG) measurements from agricultural systems to upload their data to the database. Information in this database is freely available to the public for use in research or other purposes based on the CCAFS Data Ownership and Sharing Agreement. SAMPLES was a digital platform launched in 2014 by CCAFS, SAMPLES aimed to address the dearth of reliable information about GHG emissions from agriculture in tropical countries. SAMPLES scientists work with developing countries to improve data on agricultural GHG emissions and mitigation potentials for smallholder agriculture. CCAFS coordinated SAMPLES in collaboration with CGIAR centers and scientists, and global and regional partners.